Web & android based CCTV maintenance application at PT. CCTV Palace - Harefa, Brian Spencer; Dewi, Rofiqoh (Institute of Computer Science (IOCS), 2024)
PT. Istana CCTV operates in the field of sales and services. Products sold include finger print, CCTV, access doors, hotel locks and so on. The services provided are product installation, maintenance and repairs. The problem that occurred was PT. Istana CCTV is unable to respond to customers' CCTV maintenance requests because the number of technicians is limited. On the other hand, PT. CCTV Palace often complains that CCTV maintenance requests are not immediately contacted and have to wait for the maintenance schedule. Therefore, an appropriate method is needed to increase sales turnover so that PT. CCTV Palace is making progress. The application of the FCFS method is very appropriate in Customer CCTV Maintenance services. Consumers who are the first to book CCTV Maintenance will be served first. The FCFS method is a scheduling algorithm with the characteristics of prioritizing processes that are submitted first, first come first served. So, the process that arrives first will be executed first.